Mount Bromo Eruption Disaster Preparedness With Android Mobile Based Application - Fadly - Usman; Septiana - Hariyani; Eddi Basuki Kurniawan; Mukhamad - Fathoni; Fadhilatus - Shoimah (Journal of Innovation and Applied Technology, 2020)
In the last 10 years, Mount Bromo has erupted three times; 2010, 2015, and 2019. Using the smartphone application as the Mount Bromo information facilities are one of an effort so that people and tourists can activate if an eruption occurs. There is important information about features made in the application such as distribution shelters, evacuation routes, health centers, photos, videos, and other important information. Assessment results in the application interface, the information conveyed, and also the features offered show that the application is very useful and gives a new perspective in conveying accurate information to the public and also tourists. The community satisfaction level is also quite good with the services provided by the Bromo preparedness application. Great expectations from the public and also respondents can see Mount Bromo further through CCTV cameras that are directly connected to the Android application.